Enhancing harvesting efficiency of Tetraselmis sp. biomass from aquaculture wastewater via electrocoagulation technology - Dang, Thi Thanh Loc; Van Tuan, Le (Hue University Journal of Science: Natural Science, 2024)
Harnessing nutrients in wastewater to cultivate microalgal biomass offers significant industrial and environmental benefits. However, the tiny size of marine microalgae Tetraselmis sp. makes traditional filtration methods ineffective, leading to high harvesting costs and energy consumption. This study deals with electrocoagulation and flocculation in recovering Tetraselmis sp. biomass from aquaculture wastewater, both individually and in combination, regarding their effectiveness. The results show that with an algal density of 1.16 ± 0.28 × 106 cells/mL in shrimp farming wastewater (salinity 25.0 ± 1.8‰, pH 8.3), combining flocculation (2.5 mg chitosan/L, pH adjusted to 8.2) with electrochemical treatment (TiO2 and RuO2-IrO2-TiO2 electrodes, 12 V, 3.5 A) achieved a recovery efficiency of 92% after 21 min. This method also minimized cell damage, yielding biomass with 8.5% protein, 2.4% lipid, and 23.9% carbohydrate. However, when applied individually, electrochemical treatment attained a recovery efficiency of only 37%, and flocculation reached an efficiency of 22%. These findings highlight the significant potential of electrocoagulation for harvesting Tetraselmis sp. biomass from aquaculture wastewater.